2022
DOI: 10.1007/s12445-022-1439-5
|View full text |Cite
|
Sign up to set email alerts
|

Snelle aanpassing praktijkorganisatie tijdens de coronapandemie

Abstract: Samenvatting Huisartsenpraktijken pasten tijdens de coronapandemie hun organisatie aan, mede op basis van informatie en adviezen van hun beroepsorganisaties. De aanpassingen waren noodzake-lijk om de zorg voor patiënten zo veel en zo veilig mogelijk doorgang te laten vinden, vaak op afstand. De pandemie zelf, de zorg op afstand en de strakkere geleiding van de patiëntenstroom zetten de kwaliteit van zorg en de patiëntveiligheid onder druk. De toegankelijkheid van de praktijken was soms beperkt, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The confusion around communication left the interviewed GPs feeling that some PHSMs and patient reluctance led to care postponement with sometimes devastating consequences. This confirmed the findings of earlier studies, demonstrating that most Belgian and Dutch practices faced a delayed care process in patients with urgent conditions [25,31]. The concerns of the interviewed GPs also aligned with the previous research that indicated high rates of unmet healthcare needs in patients during COVID-19 [32].…”
Section: Main Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…The confusion around communication left the interviewed GPs feeling that some PHSMs and patient reluctance led to care postponement with sometimes devastating consequences. This confirmed the findings of earlier studies, demonstrating that most Belgian and Dutch practices faced a delayed care process in patients with urgent conditions [25,31]. The concerns of the interviewed GPs also aligned with the previous research that indicated high rates of unmet healthcare needs in patients during COVID-19 [32].…”
Section: Main Findingssupporting
confidence: 89%
“…However, this finding contradicted the results of the cross-sectional PRICOV-19 study in The Netherlands [24]. More precisely, the Dutch PRICOV-19 study data showed that most practices relied on information from the independent research body, the 'National Institute for Public Health and the Environment', and professional organizations, instead of the government [25]. Moreover, the GPs from this study experienced challenges in staying up to date on PHSMs because of the rapidly changing care guidelines.…”
Section: Main Findingsmentioning
confidence: 70%
“…In other nations, the observed rise of video teleconsultations was even more meaningful. A 2022 study by Groenewegen et al assessed the PRICOV-19 questionnaire data of 155 Dutch GP practices [11]; the authors found that teleconsultations increased greatly during the COVID-19 pandemic, particularly video consultations (rising from 6% to 65% of practices in pre-vs. post-pandemic levels).…”
Section: Aaem Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%
“…This impact varies by country, providing the opportunity to learn from each other [ 2 , 3 ]. General practices (GP practices) across Europe have adapted their organization [ 4 , 5 ]. These adaptations are multiple and concern ways of dealing with specific challenges in the care for COVID-19 patients, controlling patient flows, keeping regular care going, implementing procedures for infection prevention, etc.…”
Section: Introductionmentioning
confidence: 99%